2013
DOI: 10.1093/annonc/mds515
|View full text |Cite
|
Sign up to set email alerts
|

ARIX: A randomised trial of acupuncture v oral care sessions in patients with chronic xerostomia following treatment of head and neck cancer

Abstract: Eight sessions of weekly group acupuncture compared with group oral care education provide significantly better relief of symptoms in patients suffering from chronic radiation-induced xerostomia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(134 citation statements)
references
References 25 publications
3
114
0
5
Order By: Relevance
“…The results of this case study also support previous studies that found acupuncture to be effective in stimulating saliva and improving xerostomia [12][13][14][15][16]. This case study differs from prior studies by reporting the use of a combination of manual acupuncture, auricular acupuncture, and electro-acupuncture looking specifically at the impact on odynophagia.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results of this case study also support previous studies that found acupuncture to be effective in stimulating saliva and improving xerostomia [12][13][14][15][16]. This case study differs from prior studies by reporting the use of a combination of manual acupuncture, auricular acupuncture, and electro-acupuncture looking specifically at the impact on odynophagia.…”
Section: Discussionsupporting
confidence: 83%
“…It has been found in previous studies to be effective in reducing dysphagia symptom severity in head and neck cancer patients [8][9][10][11]. Acupuncture has also been found in previous studies to be effective in stimulating saliva and improving xerostomia [12][13][14][15][16]. Although previous studies have reported the use of acupuncture on dysphagia and xerostomia following chemoradiation therapy in head and neck cancer; to our knowledge, no one has previously reported the use of acupuncture looking specifically at the impact on odynophagia, or painful swallowing.…”
Section: Introductionmentioning
confidence: 95%
“…According to Simcock et al, marked alleviation of dryness can be observed as early as after eight acupuncture sessions. The acupuncture-treated group showed improvement when compared to the controls, in whom education regarding oral hygiene was the only form of intervention [49].…”
Section: Treatment Of Xerostomiamentioning
confidence: 87%
“…Alternative modes of therapies reported for radiation induced xerostomia include hyperbaric oxygen (HBO), acupuncture, and electro stimulation. But long term results from these still warrant evidences 29 . New improvements in radiotherapy would aim for better conformed radiation beam to the best fit of the lesion with reduced volume of normal tissue exposure.…”
Section: Pharmacological and Technological Advancementsmentioning
confidence: 97%